Symmetrical carbazole–fluorene–carbazole nematic liquid crystals as electroluminescent organic semiconductors. Issue 7 (28th May 2018) - Hu, Guang; Billa, Muralidhar Reddy; Kitney, Stuart P.; Kelly, Stephen M.
ABSTRACT: A series of novel symmetrical carbazole–fluorene–carbazoles has been synthesised using simple and highly efficient reaction pathways. The correlation between their molecular structures, differing in the length of the alkyl chains in the lateral position attached to a 2, 7-disubstituted fluorene moiety in the molecular core and/or differing in the length of alkoxy chains at the terminal positions of 2, 7-disubstituted carbazole moieties, was investigated. Their mesomorphic behaviour, transition temperatures, energy levels and band gaps were measured. A test organic light-emitting diode incorporating one of these compounds exhibits blue electroluminescence. GRAPHICAL ABSTRACT: